Perundungan di Dunia Maya sebagai Perilaku Menyimpang: Analisis Isi Komentar dalam Konten Youtube Keke Bukan Boneka pada Kanal Rahmawati Kekeyi Putri Cantikka - Reza Amarta Prayoga (Jurnal Kawistara, 2022)
The comment column as an expressive forum on YouTube video sharing media is often used as a ground by netizens to stab comments - comments about "bullying cattle". Killing personal characters, dropping people's dignity, and negative comments tend to be rude, becoming decorations that are easily found and accessed in the comments column on YouTube. This paper specifically describes the behavior of netizens in bullying on Rahmawati Kekeyi Putri Cantikka's youtube channel on the content of the song Keke Bukan Boneka. The method used is descriptive qualitative. The form of data presented in this study is commented (responses or reviews) from citizens contained in the youtube channel. The presentation of the data analysis network in the form of comments using an online application, namely https://netlytic.org, and interpreted based on the theory of cyberbullying behavior proposed by Willard and the theory of deviant behavior from the combination of perspectives of James Vender Zender, Bruce J Cohen, and Robert M.Z. Lawang. The results of this study show that first, the content of the song Keke Bukan Boneka is used as an arena decorated with flaming, harassment, and denigration-type bullying comments on the figure of Kekeyi and trapped in a vortex of deviant behavior. Second, the network of bullying accounts is involved in enlivening the comment column, allegedly as a way to go viral the content of the song. Third, behind the exploitation that accompanied the bullying of Kekeyi, it turned out to be a commodity object to get monetization in the form of fantastic income from YouTube.